IMPLEMENTASI FLIPPED CLASSROOM DITINJAU DARI PENGUASAAN MATERI DAN KEMANDIRIAN BELAJAR MAHASISWA DALAM MATA KULIAH TEKNOLOGI PEMBELAJARAN - Husnawati, Zulfa (Universitas Muhammadiyah Ponorogo, 2023)
Flipped Classroom is one type of blended learning model. In Flipped Classroom, learning activities are done in reverse. Material presentation is carried out online via Gclassroom, WaG. The material presented by the lecturer is in the form of presentation slides, articles, learning videos, or other relevant links and sources about the material. While learning activities focus on knowledge exploration, confirmation of understanding, discussion, questions and answers, and assignments. The purpose of this study is to determine the results of the mastery of material review, and learning independence after implementing Flipped Classroom in Learning Technology courses at UIN Sayyid Ali Rahamatullah Tulungagung. In the implementation of Flipped Classroom, lecturers send material links, students are asked to access and study the material that has been provided before face-to-face learning activities are carried out. The results of the Flipped Classroom Implementation in terms of student material understanding obtained a score of 75.73% and fell into the â€œVery goodâ€ category. The results of the Flipped Clasroom Implementation in terms of student learning independence obtained a score of 75.75% and fell into the â€œVery goodâ€ category